Munda make over series II - Chilambe, Pedro Anglaze; Ghosh, Aniruddha (2024)
MMO Series II KAP & Audience Measurement data show a continued strong shift to preference for agricultural information on TV. • MMO amplified viewership grew from 1.9 million in Series I to 2.3 million in Series II. • A third of MMO viewers said that they found TV to be the most useful source of farming and agricultural information. • Valued topics in MMO Series II were: pest & disease management, climate information, improved seed varieties, financial literacy, good agricultural practice and gender considerations.